2000
DOI: 10.1007/s004180000223
|View full text |Cite
|
Sign up to set email alerts
|

Novel mutant Semliki Forest virus vectors: gene expression and localization studies in neuronal cells

Abstract: Semliki Forest virus vectors (SFV) are suitable for high-level transgene expression in neuronal tissue, both in vitro and in vivo. Cortical and hippocampal primary neurons in culture are efficiently infected resulting in 75-95% of GFP-positive cells, and injection of SFV vectors into hippocampal slice cultures revealed a highly neuron-specific expression pattern with more than 90% of the infected cells being neurons. Here, we present novel SFV vector mutants and describe their infection patterns obtained in cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 67 publications
(34 citation statements)
references
References 16 publications
1
33
0
Order By: Relevance
“…2). In agreement with these results, it has been reported that BHK cells infected or transfected with SFV cytopathic and non-cytopathic vectors are able to express higher levels of recombinant proteins when cultured at 31-33 °C compared to 37 °C [14,15,34].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…2). In agreement with these results, it has been reported that BHK cells infected or transfected with SFV cytopathic and non-cytopathic vectors are able to express higher levels of recombinant proteins when cultured at 31-33 °C compared to 37 °C [14,15,34].…”
Section: Discussionsupporting
confidence: 82%
“…These mutant vectors have been developed from alphaviruses that include Sindbis virus (SIN) [11,12], Semliki Forest virus (SFV) [12][13][14][15][16], and Venezuelan Encephalitis virus (VEE) [17]. Some of these mutant vectors can be used to generate RNA-based stable mammalian cell lines if a selection gene is included in the replicon [18].…”
Section: Introductionmentioning
confidence: 99%
“…7). We used a non-cytotoxic Semliki Forest Virus mutant (SFV(PD)) to introduce rTASK channel subunits into cultured neurons (53). Hippocampal neurons (7 DIV) infected with control virus, bearing only EGFP, were highly fluorescent as early as 5-h postinfection.…”
Section: Transfer Of K ϩ -And Ph-dependent Cell Death To Hippocampal mentioning
confidence: 99%
“…To obtain nontoxic virus vectors with high infection rate, we generated a mutant form of pSFV1 vectors, as reported previously (Lundstrom et al, 1999(Lundstrom et al, , 2001). The SacI-XbaI fragment from pSFV1 (Invitrogen, Carlsbad, CA) was subcloned into the pGEM7Zf ϩ vector (Promega, Madison, WI).…”
Section: Construction Of Psfv(pd)-gfp Vectors and Packaging Of The Rementioning
confidence: 99%